Adenovirus Type 7 causing severe lower respiratory tract infection in immunocompetent adults: a comparison of two contrasting cases from an intensive care unit in North West England. (October 2019) - Wingfield, Tom; Dearden, Luke; Calvert, Pete; Osanlou, Orod; Johnston, Brian; Chawla, Anu; Hart, Ian; Thompson, Catherine; Turtle, Lance; Wenstone, Richard
Abstract: Objectives: Severe lower respiratory tract infection caused by adenovirus is well described in immunocompromised hosts and can cause significant morbidity and mortality. We compare and contrast the clinical presentation, radiological, and virological features of two rare cases in immunocompetent adults admitted to an intensive care unit in a large, teaching hospital in North West England. We then provide a concise, comprehensive literature review. Methods: The first case was a 35-year old female asthmatic who presented with respiratory distress and pneumonitis during peak influenza season, and recovered after a prolonged hospital stay. The second case was a 73-year old male who presented with diarrhoea, vomiting, and general malaise outside of influenza season, developed respiratory compromise, and died. Adenovirus type 7 was identified in bronchoalveolar lavages and plasma samples of both patients, each of whom received cidofovir. No other infectious aetiology was identified. Results: Clinical and radiological features of severe lower respiratory tract adenoviral infection are similar to other infectious causes of pneumonia and ARDS, including severe influenza. This can create diagnostic uncertainty, especially during influenza season. Positive adenovirus polymerase chain reaction results can support a diagnosis of severe lower respiratory tract adenovirus infection in patients with a clinically compatible syndrome and no other identified aetiology, with higher viral loads being associated with worse prognosis. Although treatment is predominantly supportive, early use of cidofovir may improve outcomes. Conclusions: These rare cases highlight that severe lower respiratory tract adenoviral infection should be considered in the differential diagnoses of immunocompetent patients presenting with pneumonia and ARDS. Highlights: Severe lower respiratory tract adenovirus infection requiring critical care admission is rare in immunocompetent adults. Evidence concerning diagnosis and management of immunocompetent adults with adenovirus severe lower respiratory tract infection (sLRTI) is limited. We present rare cases of severe lower respiratory tract adenovirus infection in immunocompetent adults, on a critical care unit. Immunocompetent patients with adenovirus sLRTI may present with pneumonitis and acute respiratory distress syndrome (ARDS) Clinical features of sLRTI are difficult to distinguish clinically and radiologically from other causes of pneumonitis, including severe influenza.